Experimental validation of a nonlinear model predictive controller regulating the acetate concentration in fed‐batch Escherichia coli BL21(DE3) cultures. Issue 1 (7th March 2022) - Abadli, Merouane; Dewasme, Laurent; Tebbani, Sihem; Dumur, Didier; Vande Wouwer, Alain
Abstract: Fed‐batch cultures of Escherichia coli are commonly used for the production of biopharmaceuticals. However, productivity can be adversely affected by the production of acetate inhibiting the cell respiratory capacity. In this study, a nonlinear predictive control is developed based on a process model, and an unscented Kalman filter for estimating the evolution of the glucose and acetate concentrations. The control objective is to regulate the acetate concentration at a low level, so as to maintain the culture close to the edge between the fermentative and respirative regimes. The control strategy is tested in simulation and in lab‐scale experiments, demonstrating its feasibility and performance. Abstract : Increasing productivity in fed‐batch Escherichia coli cultures can be achieved by monitoring the acetate concentration, whose accumulation inhibits cell growth. This study presents a nonlinear predictive control structure to regulate the acetate concentration at a low level. The controller is coupled to an unscented Kalman filter estimating the glucose and acetate concentrations evolution. The control strategy is validated in simulation and lab‐scale experiments, demonstrating its feasibility and performance.